Comprehensive Physiology 2015
DOI: 10.1002/cphy.c150011
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone, Hormone Analogs, and Angiogenesis

Abstract: Modulation by thyroid hormone and hormone analogs of angiogenesis in the heart after experimental infarction, and in other organs, has been appreciated for decades. Description of a plasma membrane receptor for thyroid hormone on the extracellular domain of integrin αvβ3 on endothelial cells has revealed the complexity of the nongenomic regulation of angiogenesis by the hormone. From αvβ3, the hormone directs transcription of specific vascular growth factor genes, regulates growth factor receptor/growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 83 publications
1
49
0
Order By: Relevance
“…This should be particularly relevant to GBM because of its extensive vascularity. NDAT inhibits actions of vascular endothelial growth factor (VEGF) [22, 46], basic fibroblast growth factor (bFGF) [47], platelet-derived growth factor (PDGF) (S.A. Mousa, unpublished observations), and epidermal growth factor (EGF) [48]. Depending on the growth factor, these effects can involve gene transcription, growth factor release, or inhibitory crosstalk between the thyroid hormone-tetrac receptor on integrin αvβ3 and the vascular growth factor receptors clustered with the integrin on or in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should be particularly relevant to GBM because of its extensive vascularity. NDAT inhibits actions of vascular endothelial growth factor (VEGF) [22, 46], basic fibroblast growth factor (bFGF) [47], platelet-derived growth factor (PDGF) (S.A. Mousa, unpublished observations), and epidermal growth factor (EGF) [48]. Depending on the growth factor, these effects can involve gene transcription, growth factor release, or inhibitory crosstalk between the thyroid hormone-tetrac receptor on integrin αvβ3 and the vascular growth factor receptors clustered with the integrin on or in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effectiveness of NDAT involves pro-apoptotic activity and disruption of transcription of genes essential to a number of cancer cell survival pathways. The anti-angiogenic activity of NDAT involves disordering by several mechanisms of actions of endogenous growth factors, such as vascular endothelial growth factor (VEGF) [22], basic fibroblast growth factor (bFGF; FGF2) [22] and platelet-derived growth factor (PDGF) (S.A. Mousa, unpublished observations). NDAT also downregulates expression of the epidermal growth factor receptor ( EGFR ) gene [23].…”
Section: Introductionmentioning
confidence: 99%
“…For ovarian cancer patients, a significant increase was found only for T 4 ( P = 0.050) [15]. Extensive in vitro studies reviewed elsewhere have suggested that T 4 may play a more important role than T 3 in stimulating cancer cell proliferation [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effect of thyroid hormone on cancer cell proliferation is largely expressed via a cell surface receptor for the hormone on the extracellular domain of integrin αvβ3 [26], rather than via nuclear thyroid hormone receptors (see below). We showed in the current studies that thyroid hormones stimulated proliferation of ovarian cancer cells with high levels of integrin αvβ3 through phosphorylation of ERK1/2 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TRβ1 and TRα, another binding site of thyroid hormone is the cell surface integrin α v β 3 . Physiologic concentrations of thyroid hormones ( l ‐thyroxine (T 4 ) and 3,5,3‐triiodo‐ l ‐thyronine (T 3) ) bind to an integrin α v β 3 receptor on the plasma membrane, and, in vitro , stimulate the growth of various tumor cell lines, including glioma cells, medullary thyroid and papillary thyroid cancer cells, lung cancer cells, breast cancer cells, colorectal cancer cells, pancreatic cancer carcinoma, renal cell cancer cells, and ovarian cancer cells . The growth of tumor cells promoted by thyroid hormone is dependent on activated ERK1/2, and an inhibitor of ERK1/2, PD 98059, inhibits the proliferative activity of the hormone.…”
Section: Steroid Hormonesmentioning
confidence: 99%